Percussion Pattern of Terebang Gede in Panggung Jati Studio, Panggung Jati Village, Serang - Suhaya, Suhaya; Rachman, Abdul; Sinaga, Syahrul Syah; Alfayad, Dandi Musa (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2020)
The characteristics of a region become an identity that is certainly inseparable from the noble values it adheres to, including religious values as the foundation for the formation of art of terebang gede in the Panggung Jati studio, Panggung Jati village, Serang, Banten. This study aims to describe the percussion patterns in the art of Terebang Gede both in text and context by using a qualitative paradigm with descriptive analytical methods. As a highlighted theory, ethnomusicology is used to analyze the existence of music in a culture, both from physical aspects and socio-cultural aspects. The data collection technique is done by interview, documentation study, and literature study. The data analysis stages are carried out in the order of data collection, data reduction, data organizing into a pattern, category, and description into basic descriptions that lead to the concluding process. The results showed that the percussion pattern of terebang gede is very simple. The percussion patterns on all existing musical instruments, such as the musical instrument of koneng, kempul, penganak (bibit), interlude, and bass (terebang gede), still follow the framework of the percussion Ã¢â‚¬Å“standardÃ¢â‚¬Â which is hereditary from previous generations. Until now, this accompaniment without the development of rhythmic variations has been used to accompany syair or sholawat Al-Barzanjiwith with tones of Sundanese-style songs of the salendro type. Changes in accompaniment were not made because this performance was only performed on special occasions for Muslims to broadcast and support worship which was not intended as entertainment music.